Effectiveness of strategies for reducing absenteeism due to muscular disorders in a philanthropic hospital - Duarte, Cleber Ercolin; Netrovsky, Patricia de Paula; Benedito, Marileise Aparecida Pereira de Lima (Seven Editora, 2023)
Musculoskeletal disorders are an important reason for absenteeism, reaching around 27 million Brazilians (FERREIRA R.C., 2012). Within this panorama, it is evident that the workload that exists in hospital functions can be considered an important source of illness to the worker, a fact that directly reflects the absence of the employee in their shifts (KUNRATH G.M., 2021). This phenomenon known as absenteeism due to illness situation is one of the biggest problems related to the management of human resources in hospitals (MARQUES D.O., 2015). DOI:https://doi.org/10.56238/devopinterscie-255